EVALUATION OF THE LATVIAN FLAX GENETIC RESOURCES AND PERSPECTIVE OF THEIR UTILISATION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Flax (Linum usitatissimum L.) is one of the oldest fibre and oil crop in Europe, including Latvia. In the middle of the last century growing areas of this crop was reduced dramatically. Nowadays flax attracted a great interest again as a fibre and oil processor, as well as a crop for diversification of agriculture and, in the same time, as a crop for producing high quality fibre for industry, high quantity oil for biofuel and high quality oil for feeding, food, and pharmacy (source of α-linolenic acid, linoleic acid and vitamins). We evaluated all available flax accessions of the Latvian origin and number of their hybrid lines. Agronomically important qualitative and quantitative traits, such as total plant height, technical plant height, number of seed vessels, logging resistance, vegetation period, yield of straws and seeds, 1000 seeds weight, bast fibre, number of seeds in a seed vessel, oil content and rust resistance gene L alleles L2 and L9 were recorded. Results of the field trials of two last years were summarized. Local accessions are useful as a source for breeding to adaptation of flax varieties to the local Latvian conditions. With use of molecular methods flax rust resistance allele L2 and L9 were found in eleven accessions.